OUTER-SPHERE ADSORPTION OF PB(II)EDTA ON GOETHITE - IMPLICATIONS FOR ADSORPTION OF METAL IONS IN NATURAL WATERS - Bargar J.R.; Persson P.; Brown G.E. (My University, 1999)
Fourier transform infrared (FTIR) and extended X-ray absorption fine structure (EXAPS) spectroscopic measurements were performed on Pb(II)ethylenediaminetetraacetic (EDTA) adsorbed on goethite as a function of pH (4-6), Pb(II)EDTA concentration (0.11-72 μM), and ionic strength (16 μM-0.5 M). FTIR measurements show no evidence for carboxylate-Fe(III) bonding or protonation of EDTA at Pb:EDTA = 1:1. Both FTIR and EXAFS spectroscopic measurements suggest that EDTA acts as a hexadentate ligand, with all four of its carboxylate and both of its amine groups bonded to Pb(II). No evidence was observed for inner-sphere Pb(II)-goethite bonding at Pb:EDTA = 1:1. Hence, the adsorbed complexes should have composition Pb(II)EDTA2-. Because substantial uptake of PbEDTA(II)2- occurred in the samples, we interpret that Pb(II)EDTA2- adsorbed as outer-sphere complexes and/or as complexes that lose part of their solvation shells and hydrogen bond directly to goethite surface sites. We propose the term ''hydration-sphere'' for the latter type of complexes because they should occupy space in the primary hydration spheres of goethite surface functional groups and to distinguish this mode of sorption from common structural definitions of inner- and outer-sphere complexes. The lack of evidence for inner-sphere EDTA-Fe(III) bonding suggests that previously proposed metal/ligand-promoted dissolution mechanisms should be modified, specifically to account for the presence of outer-sphere precursor species.